MANAJEMEN KERJA PENYAPU JALAN DI KOTA PEKANBARU - Noviani, Ellin; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is a study describing a road sweeper Work Management workers in charge of cleaning the main streets in the city of Pekanbaru. Based on field observations, problems that occur is the lack of control by the foreman of personal protective equipment for health and safety street sweeper. The research objective is to determine and analyze the Work Management road sweepers who were recruited by the Department of Hygiene and Pekanbaru city as well as to identify and analyze the factors that affect Work Management Sweepers Road in the city of Pekanbaru.The concept used is the theory that management at the start of the planning, organizing, implementation and monitoring. This study uses qualitative research methods with an assessment of descriptive data. In data collection the author uses interview, observation and documentation. By using key informants as a source of information and analysis of data.The results of this study lead to the conclusion that the street sweeper work management in the city of Pekanbaru conducted by the Department of Hygiene and Pekanbaru in organizing a street sweeper performance includes the steps of planning, organizing, implementing, and monitoring. Then the factors that affect the pace Department of Hygiene and Pekanbaru, factors expected implementation of standard operating procedures foreman crack down street sweepers workers who work not in accordance with standard operating procedures. Factors training / socialization earmarked for road sweepers workers so that workers know the importance of occupational safety and health.Keywords: Management, labor, road sweepers, occupational safety and health,